God in cosmic history: where science & history meet religion - Peters, Ted (Anselm Academic, 2017)
Perhaps inadvertently, historians have often eliminated the religious chapters--those episodes in history during which human insights into transcendence and divinity have shaped human consciousness--from our planet's story. This book tells the story of cosmic history as big historians tell it, beginning with the big bang, and explores the question of God hidden beneath this story. The book pauses on the Axial Age of human history: a moment during the first millennium BCE in which questions of transcendence first simultaneously arose in distinct locations around the world. By exploring this threshold in cosmic history, the author demonstrates the way the arrival of the God question marked a radical new human consciousness, one that ultimately laid the groundwork for the modern age.--